Characteristics of and factors influencing cognitive impairment in adolescent patients with first-episode depression. Issue 4 (2nd October 2018) - Peng, ShiYue; Li, Jing; Wu, ZuQin; Cao, Wan; Jian, YuHan; Lu, Yue; Pei, ChangZhen
ABSTRACT: This study aims to explore the characteristics and risk factors of cognitive impairment in adolescent patients with first-episode depression. In total, 128 adolescents with first-episode depression were selected (patient group). Clinical factors, including gender, educational level, suicide risk, sleep status based on the Pittsburg Sleep Quality Index scale (PSQI), and disease duration based on Hamilton Rating Scale for Depression (HRSD), were assessed to identify risk factors. The MATRICS Consensus Cognitive Battery (MCCB) was used to assess 50 health subjects (control group). Data were statistically analyzed using the t test, χ 2 test, Pearson's correlation analysis, and stepwise multiple regression analysis in SPSS 22.0. The total MCCB score in the control group was higher than that in the patient group ( P  < 0.05), while no differences were observed on the maze test, semantic fluency, and continuous operation results ( P  > 0.05). Cognitive functional impairment in adolescent patients with first-episode depression was related to gender, educational level, suicide risk, sleep disorder, total HRSD score, and disease duration. The stepwise multiple-linear regression analysis obtained the regression equation as follows: Y1 (total MCCB points) = 82.741 + 11.897 × X3 (educational level) – 8.914 × X6 (total HRSD score) – 8.457 × X7 (total disease duration). Cognitive impairment in adolescent patients with first-episode depression was related to their gender, educational level, suicide risk, sleep disorders, HRSD score, and disease duration. Further, educational level, HRSD score, and disease duration were identified as high-risk factors.